TALAQ DALAM LINTAS MADZHAB FIKIH - Slamet Arofik; Fifin Waladatus Sholihah (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
Talaq, divorce and severing marriage ties in Islam are recognized and prescribed by law. Although basically Talaq is an act that is disliked by God of the Universe, for the benefit of husband and wife, Talaq is justified and even arranged in such a way. Therefore, the shari'a of Talaq are based on the Qur'an, al-Sunnah and Ijma'. Talaq can be done in a variety of ways and forms, sometimes using words and sometimes using writing. Using words sometimes with a special editor (sharih) and sometimes with a satire editor (kinayah). Specific words are clear words (sharih), such as the word talaq, divorce, breakup and others. Can also be in the form of satire, such as the words ba'in, haram, ithlaaq, and the like. As for other things that occupy the position of Talaq pronunciation/words are writing and signs that can be understood.